Forças Intermoleculares: abordagem nos livros de química orgânica e desenvolvimento e avaliação de um jogo educacional para a revisão do tema - Oliveira, José Mariano de Sousa (2022)
Intermolecular forces (IMFs) are weak attractive forces used to explain the interaction between matter particles. Unfortunately, several studies report the difficulties of students in understanding this concept. Based on this reality, we analyzed fifteen organic chemistry textbooks usually used in Brazilian universities to examine how the contents and exercises on IMFs are being addressed. The analysis of the books showed that all mention the IMFs. Still, They do so in a fragmented way into several chapters, not bringing enough information to create a clear image of the phenomenon in the student's mind. This poor approach to IMFs intextbooks can lead to teachers' lack of interest in approaching the subject, failing to teach thisvital organic chemistry topic. In addition, given the lack of a game that specifically addressedthe IMF theme, we developed and applied Interactions 500, a hybrid game in question and answer format, available in four languages (Portuguese, English, Spanish and French).Although the game wasdeveloped to be implemented in person, the advent of the Covid-19 pandemic made us develop a strategy for the remote use of the game. Students from the Pharmacy and Chemistry courses at the Federal University of Ceará played the Interactions 500 remotely and evaluated it. Student opinions were very positive regarding the design, content, gameplay, usability, and usefulness. Finally, the learning assessment revealed that the game promotes knowledge as well as a traditional problem solving class and, therefore, can be used as a complementary educational tool.